The effect of brand image and country of origin on consumer buying interest: case study on Yamaha NMAX motorcycle in Denpasar city - Rusmiati, Ni Nyoman; Sugiati, I Gusti Ayu; Purnami, A.A. Sri; Amerta, I Made Suniastha (International research journal of management, IT and social sciences, 2020)
Positive perceptions and consumer trust in a brand will create a good brand image. Therefore the company must be able to create an attractive brand and describe the benefits of the product under the wishes of consumers so that consumers have a positive perception of the brand. Besides, what consumers often use to consider choosing a product is the country of origin of the product. The country of origin is generally considered to be a characteristic of a product. So the purpose of this study was to determine the effect of brand image and country of origin on the purchase intention of Yamaha NMAX motorcycles in Denpasar City. The results showed that: Brand Image and country of origin have a positive and significant influence on the purchase intention of Yamaha NMAX motorcycles in Denpasar City.